STRATEGI PERUSAHAAN DALAM MENINGKATKAN EMPLOYEE EFFECTIVENESS DI PT. AGEL LANGGENG PASURUAN - jurnalmap map; Enggar Tri Cahyono; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT One of the most important elements that can support the running of a company is human resources (employees). Making a company that is the choice for employees and job seekers can be said to answer a question whether it motivates employees to remain full and engage with the company. One of the steps that the company can take is through a program engagement program. This must be managed and measured to ensure that employees are not only effective in their roles and in meeting organizational goals, but also that they are involved and motivated to play a role in the company's progress. This can be done by using several tools to measure and manage employee effectiveness PT Agel Langgeng, has made major changes in the organization's strategy through human resource development, as well as organizational change, based on the results of the 2016 and 2017 Employe Engangement Survey (EES), which revealed an increase in engagement rates from 56% to 87%. This research is qualitative research. The results of this study indicate that PT Agel Langgeng Pasuruan has implemented a strategy to create employee effectiveness. This is indicated by the opinions of employees on the company both in terms of dimensions of engagement and dimensions of enablement. Keywords: employee effectiveness, company strategy